2014
DOI: 10.1002/pola.27359
|View full text |Cite
|
Sign up to set email alerts
|

Well‐controlled ring‐opening polymerization of cyclic esters catalyzed by aluminum amido complexes: Kinetics and mechanism

Abstract: A series of aluminum dimethyl complexes 1–6 bearing N‐[2‐(pyrrolidinyl)benzyl]anilido ligands were synthesized and well characterized. The molecular structure of complex 1 determined by an X‐ray diffraction study indicates the bidentate chelating mode of the pyrrolidinyl‐anilido ligand. In the absence of a coinitiator, these complexes exhibited excellent control toward the polymerizations of ε‐caprolactone and rac‐lactide, affording polyesters with quite narrow molecular weight distributions (Mw/Mn = 1.04–1.26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…22) supported by amino-amido ligands, diamido ligands or amidinate ligands were synthesized. [94][95][96][97][98] Without any co-initiator, the aluminum dimethyl complexes 85-87 could polymerize rac-LA or ε-CL in a well-controlled manner, producing polyesters with narrow molecular weight distributions. The results suggested that the ligands in these aluminum dimethyl complexes could act as initiating groups for the ROP of rac-LA or ε-CL in a living manner.…”
Section: Aluminum Alkyl Complexes Supported By Aminoamido Ligands Dia...mentioning
confidence: 99%
“…22) supported by amino-amido ligands, diamido ligands or amidinate ligands were synthesized. [94][95][96][97][98] Without any co-initiator, the aluminum dimethyl complexes 85-87 could polymerize rac-LA or ε-CL in a well-controlled manner, producing polyesters with narrow molecular weight distributions. The results suggested that the ligands in these aluminum dimethyl complexes could act as initiating groups for the ROP of rac-LA or ε-CL in a living manner.…”
Section: Aluminum Alkyl Complexes Supported By Aminoamido Ligands Dia...mentioning
confidence: 99%
“…Amidinic catalysts have recently been used for several reactions, such as olefin polymerization (Figure , I), ring-opening polymerization of cyclic esters (Figure , II), and benzamidinate complexes have been applied in the transformation of CO 2 into cyclic carbonates (Figure , III). One of the most interesting properties of the amidinic systems is their capacity to coordinate to different metallic centers, which has allowed incorporation of different elements from the traditional transition metals and expanded the study to elements of greater abundance such as zinc (Figure , IV), magnesium (Figure , V), and aluminum (Figure , VI).…”
Section: Introductionmentioning
confidence: 99%